Venlafaxine induced hepatotoxicity in a carcinoma of breast survivor with co-morbid depression - Raj, Rajnish; Bhagat, Nisha (International Journal of Basic & Clinical Pharmacology, 2017)
Drug Induced Liver Injury (DILI) is one of the leading causes of liver damage worldwide and raises concerns about its prescription in lieu of the limited drug options available for the depression. Venlafaxine (VEN) is an antidepressant with dual neurotransmitter receptor modulations i.e., serotonin and norepinephrine reuptake inhibitor (SNRI) and having an additional benefit in management of vasomotor symptoms especially in menopausal patients where hormone replacement therapy (HRT) is contraindicated. VEN induced hepatotoxicity have been reported to occur in less than 1% of patients. Until now, less than 11 cases of VEN-related liver injuries have been reported in literature. We hereby, report a rare case of VEN induced liver injury in a 40-year-old breast cancer survivor with co-morbid depression.